1999
DOI: 10.2741/pawelec
|View full text |Cite
|
Sign up to set email alerts
|

T cells and aging (update February 1999)

Abstract: T cell immunosenescence 218effects of dysregulated immune responses in the elderly by supplementation or other approaches may result in an enhancement of their quality of life, and significant reductions in the cost of medical care in old age. FACTORS CONTRIBUTING TO IMMUNO-SENESCENCE HematopoiesisDysregulated hematopoiesis is seen in elderly individuals, raising the possibility that this could contribute to altered immune function in the aged. Hematopoiesis in man may be compromised because of a severely redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(38 citation statements)
references
References 188 publications
(212 reference statements)
1
32
0
5
Order By: Relevance
“…26 Interestingly, immunosenescence is inhibited by antioxidants indicating involvement of oxidative stress. 27 Immune cells that interact with epitopes in oxidized LDL are likely to be particularly exposed to oxidative stress. Because oxidized LDL is present in arteries already at a very early age 28 these immune response are being continuously challenged for several decades, which may further contribute to a development of immunosenescence.…”
Section: Fredrikson Et Al Apob Peptide Autoimmunity and Cvd 875mentioning
confidence: 99%
“…26 Interestingly, immunosenescence is inhibited by antioxidants indicating involvement of oxidative stress. 27 Immune cells that interact with epitopes in oxidized LDL are likely to be particularly exposed to oxidative stress. Because oxidized LDL is present in arteries already at a very early age 28 these immune response are being continuously challenged for several decades, which may further contribute to a development of immunosenescence.…”
Section: Fredrikson Et Al Apob Peptide Autoimmunity and Cvd 875mentioning
confidence: 99%
“…Age‐related changes in humans have also been described for memory CD8 + T‐cells, which provide frontline defence against viruses and tumors (Appay et al ., 2008). In particular, elderly individuals harbor a higher proportion of terminally differentiated (CD28 − ) memory CD8 + T‐cells, which exhibit strong effector functions constrained by limited proliferative capabilities in tandem with short telomeres (reviewed in Pawelec et al ., 1999). More recently, Akbar and colleagues have provided new insights into the associated molecular defects (Henson et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…320 Little insight to the mechanism of these various effects by the class-II on immune function was available until recently, when it was demonstrated that different class-II molecules varied in the efficiency with which they transduce signals from CD4 across the cell membrane, and that this variation is carried with the intracellular portion of the class-II molecule. 321 As if this were not confusing enough, the age of the donors themselves has been shown to affect T cell activation 322,323 through various mechanisms. In conclusion, the genetic effect seen to be acting on cytokine production, and implicating them as disease-associated loci in their own right, are complicated by the MHC and age.…”
Section: Cytokine Reviews Databasementioning
confidence: 99%